Determinants of foreign direct investment in Malaysia / Alia Akmar Md Nordin - Md Nordin, Alia Akmar (2015)
This paper attempts to investigate the possible factors that influence the determinants of the foreign direct investment in Malaysia. For this purpose, an times series quarterly dataset of Malaysia were used and tested using times series data regression technique over the period of 1980 to 2013. To get the differences of determinants domestic of foreign direct investment in Malaysia, all the samples were then split according to inflation rate, exchange rate, growth rate and market size (gross domestic product) of Malaysia. This result will indicate the determinants of foreign direct investment in environment in Malaysia. In this study we will determine the significant relationship between all the variable toward the foreign direct investment whether result in positive or negative.